Eksperimentasi Pembelajaran Matematika Dengan Pendekatan Problem Based Learning Dan Project Based Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Kreativitas Siswa Kelas VIII Di SMP Negeri 1 Kartasura Tahun Pelajaran 2015/2016 - Sudarmi, Titik, Prof. Dr. Bambang Sumarjoko (2017)
This study aims to test 1) The difference in the effect of learning with Problem Base Learning and Project Based Learning on learning outcomes in mathematics. 2) Differences in mathematics learning outcomes in terms of the level of creativity of student learning. 3)interaction of approach with the creativity of learners towards mathematics learning outcomes. The study design Quasi exsperimental. The population of all eighth grade students of SMP Negeri 1 Kartasura. Sampling with random cluster sampling, the sample used is class VIIIH and VIII I. Metode data collection with documentation, questionnaires and tests. Mechanical analysis by Anova two way cells are not the same, continued research Scheffe.Hasil method with a significance level of 0.05 indicates: 1) Results of mathematics learning in the class Project Based Learning is 80.21 and the average results of students' mathematics learning in the class Problem based Learning (PBL) is 69.169. The results of students in the class Project Based Learning is better than the results of student learning in the classroom Problem Based Learning. 2) The ability to think mathematically creativity heavily influence the learning of mathematics. 3) Project Based Learning approach capable of providing better mathematics learning than learning Problem Based Learning approach both for the students creative category, quite creative and less creative.